Optimalisasi Pemahaman tentang Menarche pada Kader PKK dan Remaja Putri di Desa Kemuning Lor Jember - Gandu Eko Julianto Suyoso; Bakhtiyar Hadi Prakoso; Veronika Vestine; Surya Dewi Puspita; Dina Fitriyah (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2022)
Based on the preliminary study that has been carried out, namely with several village officials. Currently, the village of Kemuning Lor still lacks socialization related to menarche education, so that many teenagers in Kemuning Lor Village, Arjasa District, Jember Regency still do not understand menarche. This of course has an impact on the reproductive health and psychology of adolescent girls because of the lack of knowledge about menarche. This community service activity will optimize the understanding of menarche among PKK cadres and young women in Kemning lor Village, with socialization activities and application learning. The result of this community service activity is an increase in knowledge about menarche for both PKK Cadres and Young Women. From the level of understanding that was previously 30% which was included in the category of high knowledge to 85% after socialization.